Incidence of thrombocytopenia in neonates receiving phototherapy for indirect hyperbilirubinemia: a prospective cohort study - Shah, Mubashir H.; Vedula, Ramya; Roshan, Reashma (International Journal of Research in Medical Sciences, 2019)
Background: Thrombocytopenia as a side effect of phototherapy has not been mentioned in the standard literature but was described briefly as isolated case reports after the phototherapy came in vogue in 1958. The purpose of this study was to find the incidence of thrombocytopenia in neonates with uncomplicated indirect hyperbilirubinemia receiving phototherapy in a referral hospital. Methods: This was a prospective cohort study conducted in a referral hospital over a period of 18 months from June 1, 2013 to November 1, 2014. Results: A total of 103 babies were enrolled. The overall incidence of post-phototherapy thrombocytopenia was 45.6% while mild, moderate and severe thrombocytopenia was present in 66%, 21.3% and 12.8% of babies respectively. The lowest platelet count observed was 31,000/mm3 but none of the neonates showed bleeding manifestations. The incidence of thrombocytopenia following phototherapy was significantly higher in preterm babies, infants who received double surface phototherapy, babies who received phototherapy for >72 hours and in babies who received phototherapy on day 2 or 3 of life. Conclusions: Neonates requiring phototherapy for hyperbilirubinemia are at risk of developing thrombocytopenia, hence the treatment should be initiated based on the standard guidelines. Unnecessary use and prolongation of phototherapy should be avoided considering the possible side effects. Platelet count should be monitored particularly in pre-term neonates receiving phototherapy. Neonates receiving double surface phototherapy and those requiring phototherapy for longer duration require more frequent platelet count monitoring.